An assessment of domestic sewage sludge in pearl millet-wheat system under saline irrigation - ANKUSH, ANKUSH; PRAKASH, RAM; LOUHAR, GANPAT (The Indian Journal of Agricultural Sciences, 2021)
The present two-year experiment (2017-19) evaluated the impact of domestic sewage sludge (SS) on yield parameters and soil nutrient status under the pearl millet-wheat system using saline irrigation. The field study consisted of three irrigation treatments [canal water (0.35 dS/m); saline water (8 and 10 dS/m)], and five fertilizer treatments [control, SS (5 t/ha), SS (5 t/ha)+50% recommended dose of fertilizers (RDF), SS (5 t/ha)+75% RDF and 100% RDF]. The results revealed a significant reduction in the biological yield and yield attributes, and protein content of both crops with increasing salinity levels of irrigation water during both the years. However, all these parameters recorded significantly highest values under 100% RDF which was statistically at par with SS (5 t/ha) + 75% RDF treatment. The soil available sulphur (S) was significantly increased with 8 and 10 dS/m EC of saline water over canal water (0.35 dS/m) irrigation. But, SS (5 t/ha) + 75% RDF obtained 36.7 and 22.3% higher available S over control and 100% RDF, respectively. No significant effects were made in DTPA-extractable micronutrients (Fe, Mn, and Cu) with saline irrigation except Zn, which was reduced under saline environment. SS added treatments obtained higher micronutrient concentration over control. Hence, SS incorporation has proven useful in sustainable crop production and improved micronutrient availability in the soil.